Female Offenders at the Confluence of Medical and Penal Discourses: Towards a Gender-Specific Criminology (1860s-1920s) - Alice Bonzom (Cahiers Victoriens et Edouardiens)
The Victorian era was characterised by a fascination with the criminal’s psyche. In the late 1860s, this interest in the criminal mind fused with scientific and medical breakthroughs to create a hybrid, cross-disciplinary field focused on understanding the criminal. Criminology was born. This polyphonic discourse incorporated many disciplines such as biology, psychiatry, anthropology and social science. This convergence of intellectual fields could be seen as gender-based. Female criminals had disobeyed the law as well as gender norms. They were double deviants whose transgression threatened society and its traditional family values. As the eugenics movement started to gain sway, a fear that these degenerate women, known as ‘inebriates’ or ‘feeble-minded creatures’, were breeding generations of atavistic deviants responsible for the decline of the British stock started to permeate society. Female recidivism was increasingly seen as a sign of mental defectiveness, a hereditary pathology. Scientific discourses revolving around the concept of ‘feeble-mindedness’ pervaded the penal sphere. In the case of women, psychiatry was intertwined with gynaecology and preconceptions about sexuality and gender. This criminological discourse led to a convergence of experts working to cure, probe, and neutralise the specific threat women posed. Rather than annihilate traditional moral explanations of crime promoted by some reformers and civil servants, scientific theories merged with them and gave birth to institutional projects such as inebriate reformatories and asylums for the mentally deficient. Criminology and penology were, in the case of women, combined with psychiatry, biology and gynaecology. The birth of male criminology can be contrasted with the emergence of female criminology, at the crossroads between science, eugenics and sexuality. The development of this new hybrid discourse had tangible consequences on the imprisonment of women in the early 20th century; these effects were particularly obvious in inebriate reformatories, asylums, and discussions around sterilisation.